Survei Tingkat Kebugaran Jasmani pada Pembinaan Prestasi Senam Aerobic Mahasiswa Pendididkan Jasmani Menggunakan Tes Kebugaran Jasmani Indonesia - Sari, Wulan; Yunitaningrum, Wiwik; Ali, Rizki Hazazi; Haetami, Mimi; Pranata, Doni (SPRINTER: Jurnal Ilmu Olahraga, 2025)
The body's ability to perform physical activities optimally is known as physical fitness. The Indonesian Physical Fitness Test (TKJI) was used in this study to determine if students enrolled in physical education had improved their physical fitness. This research uses a survey method with a descriptive quantitative approach. The research subjects consisted of regular Physical Education students. The results of the survey that has been conducted show a significant improvement in student performance. Nevertheless, the level of physical fitness among Physical Education students is still dominated by the moderate category. Out of a total sample of 8 students, or 47.05%, were categorized as good, while 9 students, or 52.95%, were in the average category. This finding indicates that despite progress, most students still need to improve their physical fitness to achieve a better category. It can be concluded that the physical fitness results for the 2024 batch are categorized as moderate.